Media Industry Organizing - Ahmed Al Khalidi (Al-Maquro\': Jurnal Komunikasi dan Penyiaran Islam, 2021)
This paper is about organizing the media industry. And discusses what an organization is, organizational structure, organizational elements and organizational charts, and how human resources in an organization are in the media. And it can be found that: An organization really needs a good vision and mission and cohesiveness in an organization, and really needs how to process professional resources so that a goal to be aspired to is achieved